Analysis of the Effect of Price, Product Quality, and Promotion on Customer Loyalty with Customer Satisfaction as an Intervening Variable in the Langgano Warkop Business in Mojoagung District - Suarga, Ajie Pandu; Kusumasari, Indah Respati (Formosa Journal of Multidisciplinary Research, 2024)
This study was motivated by sales fluctuations at Warkop Langgano Mojoagung, specifically a decrease in the number of purchases by 18.3% in February. This decline was caused by the rainy season, lack of sales promotion, and the absence of online services such as Grabfood or Gofood. Although prices are affordable and product quality is good, a lack of service and facilities can reduce customer satisfaction, potentially decreasing their loyalty. Customers. The purpose of this study is to analyze how price, product quality, and promotion impact customer satisfaction and loyalty at Warkop Langgano Mojoagung. This study uses an unlimited population and a sample of 123 respondents based on the Slovin formula. The method used is quantitative, with primary and secondary data, and analysis using SPSS at a significance level of 0.05. The results of the study indicate that customer satisfaction at Warkop Langgano Mojoagung is influenced by price, product quality, and promotion. In addition, these three factors contribute significantly to customer loyalty, both directly and through customer satisfaction. Customer satisfaction functions as a mediator that connects the influence of price, product quality, and promotion on customer loyalty.